2016
DOI: 10.1038/mi.2015.125
|View full text |Cite
|
Sign up to set email alerts
|

Induction of partial immunity in both males and females is sufficient to protect females against sexual transmission of Chlamydia

Abstract: Sexually transmitted Chlamydia trachomatis causes infertility, and because almost 90% of infections are asymptomatic, a vaccine is required for its eradication. Mathematical modeling studies have indicated that a vaccine eliciting partial protection (non-sterilizing) may prevent Chlamydia infection transmission, if administered to both sexes before an infection. However, reducing chlamydial inoculum transmitted by males and increasing infection resistance in females through vaccination to elicit sterilizing im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 30 publications
0
43
2
Order By: Relevance
“…In addition, the Th17 cells contribute to host protective immunity against bacterial pathogens and IL-17 secreted from Th17 cells was associated with protection against C . muridarum [52, 53]. Both 3MOMP and PmpG vaccines elicited a significantly increased expression of both IFN-γ and IL-17, post-vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Th17 cells contribute to host protective immunity against bacterial pathogens and IL-17 secreted from Th17 cells was associated with protection against C . muridarum [52, 53]. Both 3MOMP and PmpG vaccines elicited a significantly increased expression of both IFN-γ and IL-17, post-vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that this vaccine can stimulate antigen specific systemic and mucosal antibody responses [80]. In a recent mouse study, these authors reported that rMOMP adjuvanted with ISC can reduce the infection burden and prevent subsequent oviduct pathology [81]. This study indicated that the vaccinated animals produced different cytokines and chemokines, specially, IFN-γ, TNF-α, at the genital mucosa.…”
Section: Discussionmentioning
confidence: 98%
“…One of the major findings of this study was that antibodies generated following vaccination might contribute towards immune protection through enhancing innate and adaptive responses [81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations